1995
DOI: 10.1128/aac.39.9.2116
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of levofloxacin, singly and in combination with rifamycin analogs, against Mycobacterium leprae

Abstract: The in vitro susceptibility of Mycobacterium leprae to levofloxacin was studied by using two biochemical parameters to measure the metabolic activity of the organism. Levofloxacin consistently exhibited twofold greater bactericidal activity than ofloxacin, with the MIC being 0.75 g/ml. When combined with one of the three rifamycin analogs, synergism was obtained with KRM-1648 and rifabutin but not with rifampin.The frontline drugs against leprosy since 1947 have been either dapsone, clofazimine, or rifampin. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Also, in our previous studies, parallelism between ATP values and [ 3 H]-thymidine uptake values has been demonstrated. 14,16 Thus, it is safe to assume that the increase in metabolic activity of M. leprae observed in the present study is an indication of an increase in the cell numbers in primary cultures.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Also, in our previous studies, parallelism between ATP values and [ 3 H]-thymidine uptake values has been demonstrated. 14,16 Thus, it is safe to assume that the increase in metabolic activity of M. leprae observed in the present study is an indication of an increase in the cell numbers in primary cultures.…”
Section: Discussionmentioning
confidence: 81%
“…14,27 The method for calculating and interpreting the fractional inhibitory concentration (FIC; interaction index) has been described earlier. 16 Sampling for the assays 14 and analysis of data 16 were carried out as described earlier.…”
Section: Measurement Of Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Levofloxacin is the optically active L-isomer of ofloxacin, and the antimicrobial activity of levofloxacin is 8 to 128 times greater than that of the corresponding D-isomer (9). Levofloxacin is about twice as potent as ofloxacin against various microorganisms including M. tuberculosis, a variety of atypical mycobacteria, and M. leprae (5,7,9,15,18,20,34,38,40). At the pharmacokinetic level, both levofloxacin and ofloxacin are characterized by similar absorption rates (7,19,38,40), with a higher intracellular concentration/extracellular concentration ratio for levofloxacin compared with that for ofloxacin in cultured human macrophages (38.44 Ϯ 1.1 versus 27.1 Ϯ 0.8 g/ml, respectively) (18).…”
mentioning
confidence: 99%
“…Tuberculosis treatment unmasking leprosy: management of drug-resistant tuberculosis and leprosy co-infection G. Kama, 1 G. K. L. Huang, 2 M. Taune, 1 R. Arura, 1 L. Morris, 3 B. Kombuk, 1 A. Marome, 4 D. P. O'Brien 2,5…”
Section: Png Supplementmentioning
confidence: 99%